Striking a Balance between Centralized and Decentralized Decision Making: A School-Based Management Practice for Optimum Performance - Cornito , Celinmar M. (Innovation Journal of Social Sciences and Economic Review, 2021)
This study explores the balance between centralized and decentralized decision-making within school-based management systems. The aim is to identify how combining these approaches can enhance school autonomy, improve staff performance, and increase accountability. A systematic literature review was conducted, involving an extensive search of major academic databases. Out of 35,822 studies initially identified, 9 studies met the inclusion criteria for in-depth analysis. The selected studies were analyzed using thematic analysis to identify key patterns and themes related to decision-making in school management. Two major themes emerged from the analysis: (1) decision-making as a school-based management practice, and (2) decision-making towards school performance. The findings highlight that while decentralized decision-making empowers schools and fosters a sense of autonomy, a balanced approach incorporating both centralized and decentralized strategies is essential for optimal educational outcomes. The study concludes that a hybrid approach to decision-making, which blends centralized and decentralized methods, is most effective in enhancing school performance. This approach not only strengthens the decision-making process within schools but also aligns school management with broader educational goals. The findings suggest that increasing the involvement of internal and external stakeholders in decision-making processes can significantly boost school autonomy and accountability. Further research is recommended in two key areas: (1) the decision-making practices of school principals, and (2) decision-making related to school operating expenses and expenditures. These insights will be valuable for policymakers, school administrators, and educators aiming to improve educational outcomes through effective decision-making practices.